Internalisasi Nilai-Nilai Kewarganegaraan dalam Konteks Pendidikan Multikultural - Nimatu Sholikhah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research examines the process of internalizing civic values within the context of multicultural education in Indonesia, which faces complex challenges in forming citizens with strong national identity while appreciating diversity. The study aims to analyze effective models and strategies for internalizing civic values in multicultural educational environments and identify implementation challenges. The research methodology employs a qualitative approach with literature study analyzing relevant academic publications from 2021-2025 through qualitative content analysis techniques. Findings indicate that internalizing civic values in multicultural education requires a holistic approach integrating cognitive, affective, and behavioral dimensions through learning strategies based on local wisdom, modern technology utilization, and transformative pedagogy. Main challenges include lack of stakeholder support, policy implementation gaps, and resistance to learning paradigm changes. The research indicates the need for reconstructing civic education paradigms from indoctrination models toward reflective-contextual learning that emphasizes tolerance, inclusivity, and appreciation for cultural diversity. Research implications emphasize the importance of synergy between educational policies, teachers' roles as transformation agents, and continuous evaluation to realize civic education responsive to the challenges of Indonesia's multicultural society